Analysis of High School Students’ Chemistry Learning Motivation Using the Chemistry Motivation Questionnaire (CMQ) - Lusiana,; Erlina,; Enawaty, Eny (Hydrogen: Jurnal Kependidikan Kimia, 2026)
Learning motivation is an important factor that drives students to achieve success in their studies. This study aims to analyze the level of students' motivation in learning chemistry at SMAN 1 Siding in grades X, XI, and XII who study chemistry using the Chemistry Motivation Questionnaire (CMQ). The research method used is quantitative descriptive with data collection techniques using questionnaires and interviews involving 121 students from four classes, so the population in this study is all students studying chemistry subjects with the sampling technique using saturated sampling. The research results show that the majority of students' motivation to learn chemistry falls into the very high and high categories, with 57% in the very high category for grade X, 59% in the high for grade XI, and 69% in the high for grade XII out of 121 respondents. Based on five aspects of motivation, the three classes tend to score high on the value aspect of motivation. These findings can serve as a basis for teachers in designing more effective learning strategies that align with students' characteristics, so that the already high motivation aspects can be maintained and other motivation aspects can be enhanced to support the success of chemistry learning.